2016
DOI: 10.1163/22134808-00002532
|View full text |Cite
|
Sign up to set email alerts
|

On the Temporal Precision of Thought: Individual Differences in the Multisensory Temporal Binding Window Predict Performance on Verbal and Nonverbal Problem Solving Tasks

Abstract: Although psychology is greatly preoccupied by the tight link between the way that individuals perceive the world and their intelligent, creative behavior, there is little experimental work on the relationship between individual differences in perception and cognitive ability in healthy populations. Here, individual differences in problem solving ability were examined in relation to multisensory perception as measured by tolerance for temporal asynchrony between auditory and visual inputs, i.e., the multisensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 110 publications
0
16
0
Order By: Relevance
“…Likewise, Ward, Thompson-Lake, Ely, and Kaminski (2008) observed a significant correlation between RAT performance and the number of types of synaesthesia that a synesthete experienced. Additionally, Zmigrod and Zmigrod (2016) explored the relation- ships between problem-solving ability and the audio-visual temporal binding window, which reflects the interval during which two asynchronous sensory inputs are perceived as a single synchronous event. The results revealed a relationship between the individual's width of the multisensory temporal binding window and their ability to solve RAT and Raven's APM problems, whereby a narrower multisensory temporal binding window (i.e., one that is more precise and can sensitively detect multisensory asynchrony) predicted better performance in both tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Ward, Thompson-Lake, Ely, and Kaminski (2008) observed a significant correlation between RAT performance and the number of types of synaesthesia that a synesthete experienced. Additionally, Zmigrod and Zmigrod (2016) explored the relation- ships between problem-solving ability and the audio-visual temporal binding window, which reflects the interval during which two asynchronous sensory inputs are perceived as a single synchronous event. The results revealed a relationship between the individual's width of the multisensory temporal binding window and their ability to solve RAT and Raven's APM problems, whereby a narrower multisensory temporal binding window (i.e., one that is more precise and can sensitively detect multisensory asynchrony) predicted better performance in both tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, multisensory integration deficiency appears to be linked to problems with social skills, suggesting that multisensory integration and the temporal binding window are important for appropriate social interactions, especially when these interactions occur as a continuous flow of events (Kawakami et al, 2018). Zmigrod and Zmigrod (2016) found that a narrower temporal binding window was associated with increased sensitivity (and thus, improved performance) on Raven's APM and RAT tests. Eayrs and Lavie (2018) provide support to the notion that individuals with greater subitizing abilities have better sensitivity and accuracy when searching for changes in a task, including the detection of peripheral stimuli while attending a central task.…”
Section: Individual Differences In Audiovisual Integrationmentioning
confidence: 98%
“…This measures "reactive" flexibility and can indicate a persisting versus adapting cognitive processing style, and has been used extensively to study clinical populations such as patients with frontal-lobe damage (33), obsessive-compulsive disorder (34), and schizophrenia (35). Furthermore, (ii) the Remote Associates Test [RAT (36)], which measures individuals' capacity to flexibly retrieve semantic associations between remote conceptual representations, was also administered to provide a complementary index of a "flexibility" construct (37,38). Participants are presented with three words (e.g., cracker, fly, fighter) and must generate the compound word that links these three words (e.g., fire).…”
Section: Significancementioning
confidence: 99%